RANCANG BANGUN ALAT PENGERING SIMPLISIA BERBASIS ARDUINO - Hariyono, Muhammad Akbar; Farizi, Hafiz Al; Habibi, Ahmad Faqih; Halim, Abdul (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Simplisia is a natural medicinal raw material that has been dried. The drying process of simplicia can take 3 to 5 days. Even in extreme conditions it can reach 10 days, resulting in a decrease or even damage to the simplicia. This study aims to design an Arduino Uno-based simplisia dryer with an Arduino control program to regulate temperature. The type of research used is quantitative research, and the research method is R&D (Research and Development). The working principle of this tool uses a heater as a heater and a DHT22 sensor as a temperature monitor. If the temperature is reached, the heater will turn off and vice versa. If the temperature is below the selected temperature, then the heater will turn on by using a relay to turn off and turn on the heater until the Simplicia process is complete. The results of product testing from data in the field can be concluded as follows. Testing on the DHT2 sensor sensor 1 with the accuracy of the DHT22 sensor of 98.70%, sensor 2 with the accuracy of the DHT22 sensor of 98.70%, sensor 3 with the accuracy of the DHT22 sensor of 98.90%, sensor 4 with the accuracy of the DHT22 sensor of 98.70%, sensor 5 with the accuracy of the DHT22 sensor of 98.90%. Test tools from material experts obtained 96%, and media experts got a score of 92%, which means this tool is very feasible to use.